2021
DOI: 10.1039/d1ob02098f
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotides bearing aminophenyl- or aminonaphthyl-3-methoxychromone solvatochromic fluorophores for the enzymatic construction of DNA probes for the detection of protein–DNA binding

Abstract: Two new 2'-deoxyribonucleoside triphosphates bearing solvatochromic fluorophores were prepared and used for enzymatic synthesis of DNA probes that light-up and change colour upon interactions with proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Although two-step labeling protocols are more complex compared to direct labeling using SNTT1 with FL-dNTP, there are cases where they can serve as first choice methods: when the fluorophore moiety prevents efficient incorporation of FL-dNTP into DNA by cellular DNA polymerases. In the course of testing a wide range of commercially available FL-dNTPs (data not shown) as well as new FL-dNTPs developed in our lab, we observed that while all tested FL-dNTPs were transported into cells by SNTT1 , only some of them were efficiently incorporated into genomic DNA, and others were incorporated either inefficiently or not at all. In such cases, fluorescent labeling could, in principle, be achieved by SNTT1 -assisted delivery of dNTPs equipped with a “clickable handle”. These dNTPs need to be good substrates for intracellular DNA polymerases, and after their incorporation into DNA, the clickable handles of the nucleotides must be able to undergo a chemical post-labeling performed with suitably modified fluorophores in live cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although two-step labeling protocols are more complex compared to direct labeling using SNTT1 with FL-dNTP, there are cases where they can serve as first choice methods: when the fluorophore moiety prevents efficient incorporation of FL-dNTP into DNA by cellular DNA polymerases. In the course of testing a wide range of commercially available FL-dNTPs (data not shown) as well as new FL-dNTPs developed in our lab, we observed that while all tested FL-dNTPs were transported into cells by SNTT1 , only some of them were efficiently incorporated into genomic DNA, and others were incorporated either inefficiently or not at all. In such cases, fluorescent labeling could, in principle, be achieved by SNTT1 -assisted delivery of dNTPs equipped with a “clickable handle”. These dNTPs need to be good substrates for intracellular DNA polymerases, and after their incorporation into DNA, the clickable handles of the nucleotides must be able to undergo a chemical post-labeling performed with suitably modified fluorophores in live cells.…”
Section: Introductionmentioning
confidence: 99%
“…3c Hocek et al have reported the use of solvatochromic nucleosides containing aminophenyl-3-methoxychromone or aminonaphthyl-3-methoxychromone fluorophores in the enzymatic construction of DNA probes and demonstrated the detection of DNA–protein interactions. 3b Viscosity-sensitive nucleotides containing the dimethoxy-BODIPY fluorophore have also been reported for applications in enzymatic incorporation and as tools for DNA staining and DNA synthesis imaging. 3e Moreover, numerous base-modified fluorescent nucleosides have been developed that are being used for the detection of target DNA or RNA sequences.…”
Section: Table 1 13 C Nmr Spectroscopic Chemical Shifts...mentioning
confidence: 99%
“…Nevertheless, one of the obtained dC ATA -labeled probes showed a 9-20 fold increase of emission intensity with a concomitant 33 nm blue shift of the maxima upon interaction with the histone 3.1 and p53. A subsequent work from the same group reported FNAs based on solvatochromic 7-aryl-3hydroxy chromone fluorophores [184]. Nucleoside analogues dC AC and dT NC (figure 8) were prepared, bearing 7-aminophenyl and 7-aminonaphthyl methoxychromones conjugated to position 5 of deoxycytidine and deoxythymidine, respectively.…”
Section: Hydration-and Polarity-sensitive Fluorescent Nucleoside Anal...mentioning
confidence: 99%